Porphyromonas gingivalis Induces Bisphosphonate-Related Osteonecrosis of the Femur in Mice - Wu, Shuxuan; Li, Feng; Tan, Jingjing; Ye, Xiaoling; Le, Yushi; Liu, Nianke; Everts, Vincent; Wan, Qilong (Frontiers in Cellular and Infection Microbiology, 2022)
One of the most prominent characteristics of bisphosphonate-related osteonecrosis of the jaw(BRONJ) is its site-specificity. Osteonecrosis tends to occur specifically in maxillofacial bones, in spite of a systemic administration of the medicine. Previous studies suggested rich blood supply and fast bone turnover might be reasons for BRONJ. Yet, a sound scientific basis explaining its occurrence is still lacking. The present study aimed to explore the role of Porphyromonas gingivalis (P. gingivalis), an important oral pathogen, on the site-specificity of bisphosphonate-induced osteonecrosis and to elucidate its underlying mechanism. Mice were intraperitoneally injected with zoledronic acid (ZA) or saline for 3 weeks. In the third week, the right mandibular first molars were extracted and circular bone defects with a diameter of 1 mm were created in right femurs. After the operation, drug administration was continued, and P. gingivalis suspension was applied to the oral cavities and femur defects. The mice were killed after four or eight weeks postoperatively. The right mandibles and femurs were harvested for micro-CT and histological analyses. A poor healing of bone defects of both jaws and femurs was noted in mice injected with both ZA and P. gingivalis. Micro-CT analysis showed a decreased bone volume, and histological staining showed an increased number of empty osteocyte lacunae, a decreased collagen regeneration, an increased inflammatory infiltration and a decreased number of osteoclasts. In addition, the left femurs were collected for isolation of osteoclast precursors (OCPs). The osteoclastogenesis potential of OCPs was analyzed in vitro. OCPs extracted from mice of ZA-treated groups were shown to have a lower osteoclast differentiation potential and the expression level of related genes and proteins was declined. In conclusion, we established a mouse model of bisphosphonate-related osteonecrosis of both the jaw and femur. P. gingivalis could inhibit the healing of femur defects under the administration of ZA. These findings suggest that P. gingivalis in the oral cavity might be one of the steering compounds for BRONJ to occur.